Are NBA fans becoming indifferent to race? Evidence from the 1990s - Richard C. K. Burdekin; Richard T. Hossfeld; Janet Kiholm Smith (Claremont McKenna College, Department of Economics, 2005)
Previous work found the racial composition of NBA teams to be positively correlated with the racial composition of their metropolitan markets in the 1980s.We find continued evidence of this relationship during the 1990s, with accompanying revenue gains from the inclusion of White players on teams located in whiter areas. And, as the number of White players declined significantly throughout the decade, the revenue product of a White player actually increased on the margin. The tendency for top-performing White players in the NBA to locate in cities with larger White populations also is consistent with their higher marginal value in such locations.
Keywords: 330; customer discrimination; race; sports; National Basketball Association